2015
DOI: 10.1149/2.0551512jes
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Reduction Reaction Measurements on Platinum Electrocatalysts Utilizing Rotating Disk Electrode Technique

Abstract: Platinum electrocatalysts supported on high surface area and Vulcan carbon blacks (Pt/HSC, Pt/V) were characterized in rotating disk electrode (RDE) setups for electrochemical area (ECA) and oxygen reduction reaction (ORR) area specific activity (SA) and mass specific activity (MA) at 0.9 V. Films fabricated using several ink formulations and film-drying techniques were characterized for a statistically significant number of independent samples. The highest quality Pt/HSC films exhibited MA 870 ± 91 mA/mg Pt a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
205
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 240 publications
(216 citation statements)
references
References 123 publications
(199 reference statements)
11
205
0
Order By: Relevance
“…It disperses the catalyst particles, electrically connects the catalyst particles, enhances the conductivity locally and can act as a co-catalyst in some cases [92][93][94][95]. Most notably, the activity enhancement after Vulcan carbon addition to a conductive La 0.8 Sr 0.2 CoO 3 strongly suggests a co-catalytic role of the used carbon [96], which is also likely on conductive LaCoO 3 and La 0.8 Sr 0.2 MnO 3 as supported by kinetic modeling [95,97].…”
Section: Activity Metricsmentioning
confidence: 99%
See 2 more Smart Citations
“…It disperses the catalyst particles, electrically connects the catalyst particles, enhances the conductivity locally and can act as a co-catalyst in some cases [92][93][94][95]. Most notably, the activity enhancement after Vulcan carbon addition to a conductive La 0.8 Sr 0.2 CoO 3 strongly suggests a co-catalytic role of the used carbon [96], which is also likely on conductive LaCoO 3 and La 0.8 Sr 0.2 MnO 3 as supported by kinetic modeling [95,97].…”
Section: Activity Metricsmentioning
confidence: 99%
“…It should be noted here that both i m and the apparent i k of composite electrodes depend on the dispersion and loading of the catalytic particles [91,93,94,[104][105][106][107][108][109][110][111], which calls for optimization. Kinetic currents should be reported in the range of 10 to 80% of the limiting current and ideally below 50% [91].…”
Section: Activity Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assessment of the ECSA losses in an MEA configuration by CV is less straightforward than for RDE studies, as both the method based on integration of the H UPD charge and on the CO stripping procedure are affected by the measuring conditions. [35,61] EIS has been often coupled to I-V analyses in order to interpret the evolution of the diffusion overpotential as well as to study the ionomer degradation in the CL. [62] Young et al, for instance, monitored the CL ionic conductivity during an ADT as a function of relative humidity.…”
Section: Polarization Curves and Related Electrochemical Methodsmentioning
confidence: 99%
“…It is acknowledged that the quality of the film can substantially affect the measurement of the kinetic properties. [35] Therefore, it is possible to expect that it may affect also stability studies, although, to the authors' knowledge, no extensive work on the subject has been reported in the literature. The impact of the catalyst loading and rotation rate were studied for instance by Nagai et al, [14b] who showed that the rate of ECSA losses decreases with increasing the catalyst loading ( Figure 5) and by decreasing the rotation rate.…”
Section: Benchmarking Catalyst Stability By Thin-film Rotating Disk Ementioning
confidence: 99%